Implications of the non-detection of X-Ray emission from HD 149427 - Stute, M. (2011)
HD 149427 is a very enigmatic object. It has been classified either as a planetary nebula or as a D'-type symbiotic star. Its distance is also highly uncertain. Furthermore, HD 149427 is a potential jet source. We report the non-detection of X-ray emission from HD 149427 and explore the implications to its nature. We observed the object with XMM-Newton with an effective exposure time of 33.5 ks. The upper limit for the flux of the X-ray emission in the soft band (<2 keV) is 10^-15 erg/s/cm^2, while in the hard band (>2 keV) it is about 10^-14 erg/s/cm^2. We discuss the implication of our results in light of the possible natures of HD 149427 -- being a planetary nebula or a symbiotic star, close or very distant. The derived upper limits on the mass accretion rate of the white dwarf are untypical for symbiotic stars and may favor the picture of HD 149427 being a young PN. HD 149427 might be a symbiotic star in hibernation -- if a symbiotic star at all. We estimate the possible mass-loss rate and kinetic luminosity of the jet and find no contradiction with our upper limit of soft X-ray emission. Therefore the jet may be still present but it was too faint to be detected via soft X-ray emission.